Диалогизм как категория хронотопа в романе Евгения Гришковца «Рубашка» - Киричёк, Инна; Kіrіchеk, Inna (Східноєвропейський національний університет імені Лесі Українки, 2014)
В статье рассматривается специфика диалогизма как категории хронотопа в романе Евгения Гришковца «Рубашка». Раскрывается авторский подход к проблематике на основе классической концепции М. М. Бахтина. Хронотоп анализируется как репрезентация трёх универсалий: человека, времени и пространства, а диалогизм исследуется через призму авторского «потока сознания». Комплексное рассмотрение данных категорий интерпретирует психологизм романа в современной литературе. Сущность диалогизма романов Е. Гришковца усматривается в сопоставлении пространственно-временного континуума. Уделяется внимание сюжетной линии, которая становится местом пересечения нескольких хронотопов и отражает авторское видение проблематики. Делается вывод о том, что произведения Е. Гришковца воплощают фрагментируемый хронотоп, который не разрушает пространство и время, а основывается на субъективизме и авторском потоке сознания./ The article is devoted to the specifics of dialogism as categories of chronotopos in Yevgeniy Grishkovetz novel “Rubashka”. Author’s approach to perspective on the basis of M. M. Bakhtin’s classical theory is revealed. The chronotopos is analyzed as representation of three universal issues: person, time and space, and the dialogism is investigated through the prism of “author’s consciousness stream”. Complex consideration of these categories interprets novel psychologism in modern literature. The essence of dialogism of novels by Ye. Grishkovetz is seen in comparison of an existential continuum. The attention is put on the plot which becomes a place of the several chronotoposes crossing and reflects author’s vision of a perspective. The conclusion is maid that novels of Ye. Grishkovetz embody fragmented chronotopos which doesn’t destroy space and time, and it is based on the subjectivity and an author’s stream of consciousness.
Dialogism as Category of Chronotopos in Yevgeniy Grishkovetz Novel “Rubashka”
Киричёк И. Диалогизм как категория хронотопа в романе Евгения Гришковца «Рубашка» / Инна Киричёк // Науковий вісник Східноєвропейського національного університету. Сер. «Філологічні науки. Літературознавство». – 2014. – № 9 (286). – С. 60-63.
Keywords: хронотоп; диалогизм; время; пространство; «поток сознания»; chronotopos; dialogism; time; space; “stream of consciousness”